Myricanol rescues dexamethasone‐induced muscle dysfunction via a sirtuin 1‐dependent mechanism. Issue 2 (21st February 2019) - Shen, Shengnan; Liao, Qiwen; Liu, Jingxin; Pan, Ruile; Lee, Simon Ming‐Yuen; Lin, Ligen
Abstract: Background: Muscle atrophy and weakness are adverse effects of high dose or the sustained usage of glucocorticoids. Loss of mitochondria and degradation of protein are highly correlated with muscle dysfunction. The deacetylase sirtuin 1 (SIRT1) plays a vital role in muscle remodelling. The current study was designed to identify myricanol as a SIRT1 activator, which could protect skeletal muscle against dexamethasone‐induced wasting. Methods: The dexamethasone‐induced atrophy in C2C12 myotubes was evaluated by expression of myosin heavy chain, muscle atrophy F‐box (atrogin‐1), and muscle ring finger 1 (MuRF1), using western blots. The mitochondrial content and oxygen consumption were assessed by MitoTracker staining and extracellular flux analysis, respectively. Muscle dysfunction was established in male C57BL/6 mice (8–10 weeks old, n  = 6) treated with a relatively high dose of dexamethasone (25 mg/kg body weight, i.p., 10 days). Body weight, grip strength, forced swimming capacity, muscle weight, and muscle histology were assessed. The expression of proteolysis‐related, autophagy‐related, apoptosis‐related, and mitochondria‐related proteins was analysed by western blots or immunoprecipitation. Results: Myricanol (10 μM) was found to rescue dexamethasone‐induced muscle atrophy and dysfunction in C2C12 myotubes, indicated by increased expression of myosin heavy chain (0.33 ± 0.14 vs. 0.89 ± 0.21, * P  < 0.05), decreased expression of atrogin‐1 (2.31 ± 0.67 vs. 1.53 ± 0.25, * P  < 0.05) and MuRF1 (1.55 ± 0.08 vs. 0.99 ± 0.12, ** P  < 0.01), and elevated ATP production (3.83 ± 0.46 vs. 5.84 ± 0.79 nM/mg protein, ** P  < 0.01), mitochondrial content (68.12 ± 10.07% vs. 116.38 ± 5.12%, * P  < 0.05), and mitochondrial oxygen consumption (166.59 ± 22.89 vs. 223.77 ± 22.59 pmol/min, ** P  < 0.01). Myricanol directly binds and activates SIRT1, with binding energy of −5.87 kcal/mol. Through activating SIRT1 deacetylation, myricanol inhibits forkhead box O 3a transcriptional activity to reduce protein degradation, induces autophagy to enhance degraded protein clearance, and increases peroxisome proliferator‐activated receptor γ coactivator‐1α activity to promote mitochondrial biogenesis. In dexamethasone‐induced muscle wasting C57BL/6 mice, 5 mg/kg myricanol treatment reduces the loss of muscle mass; the percentages of quadriceps and gastrocnemius muscle in myricanol‐treated mice are 1.36 ± 0.02% and 0.87 ± 0.08%, respectively (cf. 1.18 ± 0.06% and 0.78 ± 0.05% in dexamethasone‐treated mice, respectively). Myricanol also rescues dexamethasone‐induced muscle weakness, indicated by improved grip strength (70.90 ± 4.59 vs. 120.58 ± 7.93 g, ** P  < 0.01) and prolonged swimming exhaustive time (48.80 ± 11.43 vs. 83.75 ± 15.19 s, ** P  < 0.01). Myricanol prevents dexamethasone‐induced muscle atrophy and weakness by activating SIRT1, to reduce muscle protein degradation, enhance autophagy, and promote mitochondrial biogenesis and function in mice. Conclusions: Myricanol ameliorates dexamethasone‐induced skeletal muscle wasting by activating SIRT1, which might be developed as a therapeutic agent for treatment of muscle atrophy and weakness.